2013
DOI: 10.1007/s12105-013-0442-3
|View full text |Cite
|
Sign up to set email alerts
|

GATA3 Immunohistochemical Expression in Salivary Gland Neoplasms

Abstract: GATA3 is a zinc finger transcription factor that regulates the normal development of many tissues and cell types. Recent studies have shown that immunohistochemical nuclear staining for GATA3 among tumors is highly restricted to carcinomas of breast and urothelial origin; however salivary gland tumors have not been tested. Given that breast and salivary gland tissues are very similar with respect to embryologic development and structure, we performed GATA3 staining on a spectrum of salivary gland neoplasms. GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(74 citation statements)
references
References 19 publications
1
71
0
2
Order By: Relevance
“…Recently, DOG1 has been demonstrated as a good diagnostic biomarker for acinic cell carcinoma; 7 it has not been extensively tested in low-grade salivary duct carcinoma or MASC. GATA3, a zinc-finger transcription factor, has recently been reported to be expressed by many salivary tumors including MASC, 8 but has not been tested extensively in low-grade salivary duct carcinoma. We report the immunohistochemical profiling of MASC and its mimics, namely acinic cell carcinoma, low-grade salivary duct carcinoma, high-grade salivary duct carcinoma, and cystic lowgrade mucoepidermoid carcinoma, with respect to mammaglobin, S100 protein, DOG1, and GATA3.…”
mentioning
confidence: 99%
“…Recently, DOG1 has been demonstrated as a good diagnostic biomarker for acinic cell carcinoma; 7 it has not been extensively tested in low-grade salivary duct carcinoma or MASC. GATA3, a zinc-finger transcription factor, has recently been reported to be expressed by many salivary tumors including MASC, 8 but has not been tested extensively in low-grade salivary duct carcinoma. We report the immunohistochemical profiling of MASC and its mimics, namely acinic cell carcinoma, low-grade salivary duct carcinoma, high-grade salivary duct carcinoma, and cystic lowgrade mucoepidermoid carcinoma, with respect to mammaglobin, S100 protein, DOG1, and GATA3.…”
mentioning
confidence: 99%
“…GATA3 is also expressed, however, in carcinomas primary to the breast and salivary gland 36 and in a smaller subset of genitourinary tract and lung squamous cell carcinomas. 148 Furthermore, GATA3 is useful in distinguishing TCC from high-grade prostatic adenocarcinomas, which are typically negative for this marker.…”
Section: Prostate Markersmentioning
confidence: 99%
“…However, the study by Gruver et al 76 reported 23% of pulmonary SCCs can be positive for GATA3. More recent studies demonstrated that GATA3 expression was seen in (1) salivary gland tumors (100% of salivary ductal carcinomas and mammary analogue secretory carcinomas), 74 (2) 80% of metastatic paragangliomas, 73 and (3) 7% of anal SCCs and 19% of uterine cervical SCCs, which tended to be focally positive. 75 Our unpublished data showed approximately 10% of pancreatic ductal adenocarcinomas can be positive for GATA3 on tissue microarray sections.…”
Section: Review Of Selected Antibodiesmentioning
confidence: 99%